Association of the 2019 Canada’s food guide food choices assessment score with 10-year cardiovascular disease risk and heart age in Canadian adults - Samer Hamamji; Daniel Zaltz; Mary R. L’Abbé (PLoS ONE, 2025)
Healthy diet plays an important role in the prevention of cardiovascular disease (CVD), which is the second leading cause of death in Canada. In 2019, Health Canada released an updated Canada’s Food Guide (CFG) which is accompanied with supportive evidence of Canada’s Dietary Guidelines (CDG) to reflect the latest evidence of the relationship between diet and prevention of chronic diseases including CVD. The Canadian Cardiovascular Society recommends the use of the Framingham risk score (FRS) to estimate the 10-year CVD risk and heart age in individuals aged 30 and older, aiding in CVD prevention interventions such as lifestyle modifications. However, the relationship between the intake of dietary choices aligned with 2019 CFG/CDG and CVD risk among Canadians was not studied. This study aims to examine the association between dietary choices assessed by a Food Choices Assessment Score (FCAS) according to 2019 CFG/CDG and 10-year CVD risk and heart age among Canadian adults. This cross-sectional study was conducted using the national Canadian Health Measures Survey (CHMS) (2016–2019) and included Canadian adults (≥ 30 years) without heart disease (n = 5,111). The 2019 CFG/CDG FCAS was calculated using the CHMS food frequency questionnaire. Canadians in the highest quintile (healthiest) of the FCAS had 55% lower odds (OR) of having high risk (≥ 20%) of estimated 10-year CVD risk (OR: 0.45; 95%CI: 0.23, 0.90) ( P trend = 0.011), and 47% lower odds of having unhealthy heart age difference (heart age > chronological age) (OR: 0.53; 95%CI: 0.30, 0.92) ( P trend = 0.02), compared to those in the first quintile (unhealthy) of the FCAS. This study indicates a strong inverse association of dietary choices as measured by the 2019 CFG/CDG FCAS with high 10-year CVD risk (≥ 20%) and unhealthy heart age (older than chronological age), estimated with the FRS.